**QUADRATIC EXPRESSION**.

1. Quadratic Expression is in the form of

^{2}+ bx + c

^{2}+3x +2,

^{2}-5x +4 ,

^{2}+5x -6 .

Factorisation of Quadratic Expression:

(a) x

^{2}+ 3x + 2 = (x + 2)(x + 1) ... using factors of 2 (1 x 2)

(b) x + 3x - 4 = (x + 4)(x - 1) ... using factors of 4 (1 x 4)

^{2}

(c) x - 3x - 4 = (x - 4)(x + 1) ... using factors of 4 (1 x 4)

^{2}

(d) x - 5x + 4 = (x - 4)(x - 1) ... using factors of 4 (1 x 4)

^{2}

(e) x - 4x + 4 = (x - 2)(x - 2) ... using factors of 4 (2 x 2)

^{2}

**Please refer to your teachers or someone else who knows about factorisation if you have problems with the technique of factorising...

2.2

**QUADRATIC EQUATIONS**.1. Quadratic Equations are in the form of ax

2. You are supposed to solve quadratic equations by factorisation, e.g.

^{2}+ bx + c = 0 where a,b,c are integers (+ve or -ve).2. You are supposed to solve quadratic equations by factorisation, e.g.

(a) x

^{2}+ 3x + 2 = 0(x + 2)(x +1) = 0

(x + 2) = 0 or (x + 1) = 0

x = -2 or x = -1

(b) x

^{2}+ 3x - 4 = 0(x + 4)(x - 1) = 0

(x + 4) = 0 or (x - 1) = 0

(c) x - 5x - 6 = 0

^{2}(x - 6)(x + 1) = 0

(x - 6) = 0 or (x + 1) = 0

x = 6 or x = -1

(d) x - 9x + 14 = 0

^{2}

^{}

(x - 7)(x - 2) = 0

(x - 7) = 0 or (x - 2) = 0

## 3 comments:

how to solve this

-3k^2+4k-1

(-3k + 1)(k - 1)= 0

(-3k + 1)= 0 or (k - 1)= 0

k = 1/3 or k = 1.

Have a nice day...

How to solve

(X+7)(x+3)+2(x+1)

Post a Comment